Case Report: Mimicking benignity: hepatic sinusoidal metastasis masquerading as diffuse liver disease in small cell lung cancer - Chen, Lujiao; Chen, Lulin; Yang, Jianfeng; Yang, Minxia (Frontiers in Oncology, 2025)
BackgroundSmall cell lung cancer is extremely aggressive. Although liver metastasis is common, cases of diffuse intra-sinusoidal metastasis leading to liver failure and death are quite rare.Case presentationThis paper reports a case of a 58-year-old male diagnosed with small cell lung cancer through a pathological biopsy, who died due to the rapid progression of liver failure caused by diffuse hepatic sinusoidal metastasis during subsequent treatment.ConclusionsDiffuse intra-sinusoidal liver metastasis originating from small cell lung cancer may serve as a clinically occult cause of liver failure. Such metastases progress rapidly, often leading to death within days to weeks. For patients with a history of malignant tumors, if imaging studies reveal diffuse liver lesions and rapidly progressing liver function abnormalities, there should be a high suspicion of diffuse hepatic sinusoidal metastasis. A timely liver biopsy should be performed to confirm the diagnosis, providing a theoretical basis for clinical diagnosis and treatment.